Competitive Dynamics in the Global Insurance Industry Strategic Groups, Competitive Moves, and Firm Performance - Schimmer, Markus; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
This book explores causes and consequences of interfirm rivalry within the global insurance industry. Based on three empirical studies, the book investigates (1) the mechanisms driving firm positioning and strategic group dynamics, (2) the impact of market shocks on firms' competitive behavior, and (3) the determinants of stock market responses to individual competitive actions. The book's insights offer important implications for academics and practitioners alike.
Theoretical Background -- Convergence-Divergence within Strategic Groups -- From Crisis to Opportunitiy: How Market Shocks Impact Interfirm Rivalry.-Performance Effects of Corporate Diverstiture Programs.
Keywords: Economics; Economics/Management Science; Insurance